The Digital Shift In The Mebel Market: How Marketing Strategies, Brand Equity, Location and Price Perception Influence Consumer Decisions - Tegar, Tegar; Citra Mulya Sari (Mabny: Journal of Sharia Management and Business, 2025)
This study examines the impact of digital marketing, strategic location, brand equity, and price perception on consumer purchase decisions in the furniture industry, focusing on Mebel Mandiri. Integrating digital transformation and behavioral economics, it offers a fresh perspective on consumer decision-making. Using a quantitative associative approach, data from 33 respondents was analyzed with SPSS 20, employing validity and reliability tests, classical assumption tests, multiple linear regression, and F and T-tests. The results indicate that digital marketing and price perception significantly influence purchasing decisions, while location and brand equity do not. However, collectively, these variables account for 72.2% (R² = 0.722) of consumer purchasing decisions, with 27.8% influenced by other factors. The study highlights that effective digital marketing strategies and competitive pricing are essential for enhancing consumer decisions. Businesses should focus on interactive and credible digital content while aligning pricing with product value. Additionally, digital marketing and price perception play a crucial role in strengthening SMEs, driving digital transformation, and fostering consumer trust. These strategies expand market reach, improve business resilience, and contribute to economic growth, job creation, and sustainable development.